Epigenetic Targeting of Glioblastoma - Romani, Massimo; Pistillo, Maria Pia; Banelli, Barbara (Frontiers in Oncology, 2018)
Glioblastoma (GB) is one of the first tumors where the biological changes accompanying a single epigenetic modification, the methylation of the MGMT gene, were found to be of clinical relevance. The exploration of the epigenomic landscape of glioblastoma has allowed to identify patients carrying a diffuse hypermethylation at gene promoters and with better outcome (G-CIMP). Epigenetic and genetic data have led to the definition of major subgroups of glioma and were at the basis of the current WHO classification of CNS tumors and of a novel classification based solely on DNA methylation data that shows a remarkable diagnostic precision. The reversibility of epigenetic modifications is considered a therapeutic opportunity in many tumors also because these alterations have been mechanistically linked to the biological characteristics of GB. Several alterations like IDH1/2 mutations that interfere with “epigenetic modifier” enzymes, the mutations of the histone 3 variants H3.1 and H3.3 that alter the global H3K27me3 levels and the altered expression of histone methyltransferases and demethylases are considered potentially druggable targets in glioma and molecules targeting these alterations are being tested in preclinical and clinical trials.